2018
DOI: 10.32607/20758251-2018-10-1-43-50
|View full text |Cite
|
Sign up to set email alerts
|

The PTENP1 Pseudogene, Unlike the PTEN Gene, Is Methylated in Normal Endometrium, As Well As in Endometrial Hyperplasias and Carcinomas in Middle-Aged and Elderly Females

Abstract: The tumor suppressor PTEN controls multiple cellular functions, including cell cycle, apoptosis, senescence, transcription, and mRNA translation of numerous genes. In tumor cells, PTEN is frequently inactivated by genetic mutations and epimutations. The aim of this study was to investigate the methylation patterns of the PTEN gene and its pseudogene PTENP1 as potential genetic markers of endometrial hyperplasia (EH) and endometrial carcinoma (EC). Methylation of the 5-terminal regions of the PTEN and PTENP1 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…For instance, Du et al (2019) revealed that DUXAP8 upregulation in colorectal cancer was induced by STAT3; SIX2 played a positive role in CYP4Z2P expression in breast cancer . Some studies demonstrated that the methylation level of pseudogenes linked to the alteration of pseudogene-derived lncRNAs' expression (Kovalenko et al, 2013(Kovalenko et al, , 2018. Hormone and hormone receptor correlated with mis-regulation of pseudogene-derived lncRNAs.…”
Section: Potential Dysregulated Mechanisms Of Pseudogene-derived Lncrmentioning
confidence: 99%
“…For instance, Du et al (2019) revealed that DUXAP8 upregulation in colorectal cancer was induced by STAT3; SIX2 played a positive role in CYP4Z2P expression in breast cancer . Some studies demonstrated that the methylation level of pseudogenes linked to the alteration of pseudogene-derived lncRNAs' expression (Kovalenko et al, 2013(Kovalenko et al, , 2018. Hormone and hormone receptor correlated with mis-regulation of pseudogene-derived lncRNAs.…”
Section: Potential Dysregulated Mechanisms Of Pseudogene-derived Lncrmentioning
confidence: 99%
“…In our previous study we demonstrated the absence of a correlation of PTENP1 methylation with the clinical characteristics of endometrial cancer (disease stage, FIGO grade, myometrium invasion) [ 23 ]. Here, we found higher frequency of PTENP1 methylation in patients over 45 years with EH and EC, which did not differ from methylation of NE in women of matched age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The antisense transcript of PTENP1 pseudogene interacts with the promoter region of PTEN gene and inhibits its expression [ 22 ]. In our previous study we have not detected methylation of the PTEN minimal promoter region in endometrial cancer [ 23 ]. However, methylation of the 5'-terminal region of PTENP1 was observed.…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequencing and mutation analysis of TCGA EC data identi ed some prominently mutated genes: p53 10 , PTEN 11 and PIK3CA 12 . Among them, PTEN was signi cantly associated with the prognosis of EC 13 . However, these analyses did not provide an in-depth analysis of the prognosis of PTEN mutation-related characteristic genes on EC.…”
Section: Introductionmentioning
confidence: 99%